Student-teachers’ identity construction and its connection with student-centered approaches: a narrative study (2018)
Eng: This book shows the paths student-teachers embark on the construction of their identies within the frame of a student-centered approach perspective. Understanding teacher identity construction suggests perceiving a broad and socially-driven dimension. In such a way , humansare contextual, political, and culturally situated to continually make sense of their"selves" on a daily-basis. Delving into teacher identity construction issues is a relevant constituent for the contininual professional development of English language teachers.